THE INFLUENCE OF MICROSOFT SWAY MEDIA ON LEARNING OUTCOMES IN NATURAL SCIENCE SUBJECTS IN GRADE V STUDENTS - Arnandi Mukhlas Arnandi; Zulfadewina (Universitas Majalengka, 2023)
Learning Natural Sciences in elementary schools is still considered a subject that is difficult to understand. This is evidenced by the scores of student learning outcomes which are still below the Minimum Completeness Criteria with a criterion score of 7.5. This study aims to analyze the influence of Sway's Microsoft learning media on student learning outcomes in Natural Sciences subjects. The research method uses quantitative research methods, a quasi-experimental model with a posttest-only control design pattern, and the type of instrument used uses a multiple choice test using 2 class samples. The experimental class uses Microsoft Sway learning media, and the control class uses conventional learning media. The results of this study indicate that the Microsoft sway learning media affects the learning outcomes of fifth-grade students in the Natural Sciences subject. This is supported by a hypothesis test with a result of N_sig < N_table with a score of 0.00 < 0.05. The results of the research obtained can be concluded that Sway's Microsoft learning media influences the learning outcomes of fifth-grade students in Natural Sciences subjects. Pembelajaran Ilmu Pengetahuan Alam di sekolah dasar masih dianggap sebagai mata pelajaran yang sulit untuk dipahami, hal ini dibuktikan dengan nilai hasil belajar siswa yang masih banyak dibawah Kriteria Ketuntasan Minimal dengan kriteria nilai 7,5. Penelitian ini bertujuan unuk menganalisis pengerauh media pembelajaran micrososft sway terhadap hasil belajar siswa pada mata pelajaran Ilmu Pengetahuan Alam. Metode penelitian mengunakan metode penelitian kuantitatif, model quasi eksperimen dengan pola posttest only control design dan jenis instrument yang digunakan mengunakan sebuah tes pilihan ganda dengan mengunakan 2 sampel kelas, pada kelas ekperimen mengunakan media pembelajaran micrososft sway dan kelas kontrol mengunakan media pembelajaran yang konvensional. Hasil penelitian ini menunjukan bahwa media pembelajaran Microsoft sway berpengaruh terhadap hasil belajar siswa kelas V pada mata pelajaran Ilmu Pengetahuan Alam, hal ini didukung dengan uji hipotesis dengan hasil nilai < dengan skor 0,00 < 0,05. Hasil penelitian yang diperolereh dapat disimpulkan terdapat pengaruh media pembelajaran micrososft sway terhadap hasil belajar siswa kelas V pada mata pelajaran Ilmu Pengetahuan Alam.